2017
DOI: 10.1002/2016ja023556
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effect for polar cap sunward plasma flows at strongly northward IMF Bz

Abstract: We use Super Dual Auroral Radar Network data to study polar cap ionospheric flow under strongly dominant positive interplanetary magnetic field Bz component. We show that the near‐noon flow along the magnetic meridian is predominantly sunward in summer. The sunward velocity increase with intensification of the external driver (the reverse convection electric field) is also faster in summer, and the rate of the increase is slightly larger for the Southern Hemisphere. The sunward flows simultaneously detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…We find the magnitude of the reverse convection cells to strengthen with increasing dipole tilt in agreement with previous empirical studies (Crooker & Rich, 1993;Pettigrew et al, 2010). Recent studies by Koustov et al (2017) and Yakymenko et al (2018) using polar radar observations confirm this seasonal preference; however, they also report a deviation of the sunward flows toward prenoon MLTs in the summer hemisphere. Our results disagree, instead suggesting a prenoon orientation for negative dipole tilt (i.e., winter-like) conditions only.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We find the magnitude of the reverse convection cells to strengthen with increasing dipole tilt in agreement with previous empirical studies (Crooker & Rich, 1993;Pettigrew et al, 2010). Recent studies by Koustov et al (2017) and Yakymenko et al (2018) using polar radar observations confirm this seasonal preference; however, they also report a deviation of the sunward flows toward prenoon MLTs in the summer hemisphere. Our results disagree, instead suggesting a prenoon orientation for negative dipole tilt (i.e., winter-like) conditions only.…”
Section: Discussionsupporting
confidence: 91%
“…Our results disagree, instead suggesting a prenoon orientation for negative dipole tilt (i.e., winter‐like) conditions only. This discrepancy could be attributed to the limited number of events considered by Koustov et al (, 3) and Yakymenko et al (, 12) compared to the much larger number of northward IMF intervals in our strongest E sw bins (Figures m–o).…”
Section: Discussionmentioning
confidence: 57%
“…As an example, we note that the effect of the Hall polarization field by latitudinal gradient might help understanding an unexplained characteristic seen in sunward flows (the reverse convection cell) reported by Koustov et al () and Yakymenko et al (). The reverse convection cell, consisting of the dawn negative and dusk positive cells, is a cell system in the dayside high‐latitude region during dominant northward IMF‐Bz and is thought to be associated with the lobe cell.…”
Section: Discussionmentioning
confidence: 99%
“…The reverse convection cell, consisting of the dawn negative and dusk positive cells, is a cell system in the dayside high-latitude region during dominant northward IMF-Bz and is thought to be associated with the lobe cell. By using the Super Dual Auroral Rader Network (SuperDARN) data (Greenwald et al, 1995), Koustov et al (2017) and Yakymenko et al (2018) showed that polar cap sunward flows between dawn and dusk reverse cells markedly shift from the noon-midnight meridian toward the prenoon sector in the summer hemisphere, while they show no such preference in the winter hemisphere.…”
Section: Clockwise Rotationmentioning
confidence: 99%
“…It is desirable to examine the influence on the convection pattern by dipole tilt angle Ψ , since Ψ has a large influence on the lobe reconnection process (Crooker & Rich, 1993; Koustov et al., 2017; Reistad, Laundal, Østgaard, Ohma, Thomas, et al., 2019; Wilder et al., 2010; Yakymenko et al., 2018). However, the correlation between Ψ and MLT of the Cluster orbit produces highly uneven sampling of the high latitude regions when Ψ is large.…”
Section: Methodsmentioning
confidence: 99%